Faktor yang Mempengaruhi Tekanan Darah pada Remaja SMA di Depok, Jawa Barat: Factors Contributing to the Blood Pressure of High School Students in Depok, West Java - Trista, Nesa; Sofianita, Nur Intania; Fauziyah, A'immatul (Universitas Airlangga, 2024)
Background: Hypertension is a major global health concern, contributing to high mortality rates among adults and the elderly. Recent trends show a substantial upsurge in hypertension prevalence among adolescents. According to the Health Office of Depok City, 78.10% of adolescents aged ≥15 years are reported to have hypertension. Hypertension during adolescence often persists into adulthood, increasing the risk of long-term morbidity and mortality. The primary contributors include unhealthy lifestyle practices and poor dietary habits. Objectives: To investigate factors associated with elevated blood pressure among adolescents in Depok City, West Java, Indonesia. Methods: A cross-sectional study was conducted with 158 adolescents selected through stratified random sampling. Data collection took place between February to April 2024. Variables assessed included family history of hypertension, nutritional status (based on Body Mass Index categories as per the 2020 Ministry of Health regulation), and stress levels (measured using the Perceived Stress Scale). Statistical analysis employed chi-square tests and multiple logistic regression. Results: Significant associations were found between hypertension and family history (p-value = 0.034), nutritional status (p-value = 0.014), and stress levels (p-value < 0.001). Multivariate analysis indicated that stress levels were the strongest determinant of hypertension (OR = 6.09). Conclusions: Stress levels significantly influence blood pressure in adolescents. Schools should prioritize regular programs addressing stress management, emotional well-being, and balanced nutrition education to reduce the risk of adolescent hypertension.